ChemInform Abstract: Synthesis of Novel, Functionalized Tricycles Utilizing the Interrupted Pummerer Reaction. Issue 18 (April 2016) - Boyd, Scott; Davies, Robert D. M.; Degorce, Sebastien L.; Groombridge, Sam; S. Scott, James; Stokes, Stephen
Abstract: The synthesis of novel functionalized pyrrolothiazolo‐pyridines, ‐pyrimidines, and ‐pyrazines is based on interrupted Pummerer reaction to effect cyclization of sulfoxide precursors.